Disparate faculty perspectives on system changes in higher education - Silva, Joaquim S. (2019)
Higher education (HE) systems around the world have experienced profound structural changes, particularly since the late 1960s to early 1970s, essentially driven by the need to expand access to tertiary education. This has resulted in a diversity of HE institutions (HEI) with different roles, missions and statuses, as well as academic staff with diverse perspectives and motivations. The present study is based on a survey undertaken in Portugal by a trade union, which aimed to collect faculty perspectives on a proposed HE reform sent out for public discussion by the government. Questions addressed the reorganization of the HEI network, the internal restructuring of HEI, the funding system and the binary divide of HEI (universities and polytechnics). The survey results showed a disparity of faculty perspectives about the proposed reform, closely related to the diversity of HEI. Respondents from lower academic categories and from smaller HEI were more opposed to reorganizing the HEI network. This reorganization was more widely accepted by university staff, who were also more in favour of a binary system than were polytechnic respondents. Although there was general agreement about the need to change the funding system, polytechnic respondents were strongly against a funding differentiation between universities and polytechnics. Despite an overall reformist trend, the enthusiasm for reforms declined substantially when the questions had a direct reference to the respondent’s region or institution. It is argued that HE expansion has driven the diversification of HEI, leading to a range of perspectives about the HE system and the way it should be changed. These conclusions may contribute to insights into other HE systems around the world where institutional diversification has been sought by public policies.